2007
DOI: 10.4037/ajcc2007.16.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward and Beliefs About Family Presence: A Survey of Healthcare Providers, Patients’ Families, and Patients

Abstract: Background Although some healthcare providers remain hesitant, family presence, defined as the presence of patients’ family members during resuscitation and/or invasive procedures, is becoming an accepted practice. Evidence indicates that family presence is beneficial to patients and their families. Objectives To describe and compare the beliefs about and attitudes toward family presence of clinicians, patients’ families, and patients. Methods Clinicians, patients’ families, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
3
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 29 publications
3
82
3
9
Order By: Relevance
“…[11][12][13][14] In the present study, 42.2% of the physicians and nurses believed that the relatives of the patient were more likely to tolerate the grief process after experiencing FPDR, although 41.2% of the participants disagreed with this idea, on the other hand, 75% of the participants in the survey believed that the FPDR process might create a traumatic experience (a psychological disorder) among the family members of the patient and only 4.9% of the participants disagreed.A study by Duran et al showed that the FPDR could be a great help to deal with the pain of losing the loved ones for the family members; the patient and the family also welcomed this, however this requires providing emotional support, explaining and interpreting the CPR operation during and after the process, as the lack of proper conditions and the presence of staff and space constraints may create problems for the process. 23 The findings in the present study revealed that many physicians and nurses were opposed to the presence of family members during the resuscitation process, and the number of individuals who agreed to this was much lower, while in some studies physicians and nurses were satisfied with the conditions. This can be due to cultural differences and the conditions and also the place where the resuscitation process is performed.…”
contrasting
confidence: 47%
“…[11][12][13][14] In the present study, 42.2% of the physicians and nurses believed that the relatives of the patient were more likely to tolerate the grief process after experiencing FPDR, although 41.2% of the participants disagreed with this idea, on the other hand, 75% of the participants in the survey believed that the FPDR process might create a traumatic experience (a psychological disorder) among the family members of the patient and only 4.9% of the participants disagreed.A study by Duran et al showed that the FPDR could be a great help to deal with the pain of losing the loved ones for the family members; the patient and the family also welcomed this, however this requires providing emotional support, explaining and interpreting the CPR operation during and after the process, as the lack of proper conditions and the presence of staff and space constraints may create problems for the process. 23 The findings in the present study revealed that many physicians and nurses were opposed to the presence of family members during the resuscitation process, and the number of individuals who agreed to this was much lower, while in some studies physicians and nurses were satisfied with the conditions. This can be due to cultural differences and the conditions and also the place where the resuscitation process is performed.…”
contrasting
confidence: 47%
“…This is different from previous studies that indicated nurses held more positive views of family presence (Jefferson & Paterson , Duran et al . , Kuzin et al . , Perry ).…”
Section: Discussionmentioning
confidence: 99%
“…, Duran et al . ). Critical care areas have typically included emergency and intensive care settings, while non‐critical care areas have included medical and surgical wards.…”
Section: Introductionmentioning
confidence: 97%
“…34 Research has drawn strong linkages between social support and physical health, 35 as well as between patients' access to family members and their levels of comfort and wellbeing during the process of physical healing. 36 On the contrary, enduring lengthy treatment for health issues alone or with limited access to friends and family can result in negative impacts on patients and their loved ones. 12,37,38 Participants, and in particular mothers, described disconnection from family as being an incredibly difficult experience, and even more so for those participants from remote and isolated reserves who had to be flown out of their communities.…”
Section: Role Of Family In Providing Social Supportmentioning
confidence: 99%